2011
DOI: 10.1007/s10498-011-9147-y
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Variation in the Optical Properties of Dissolved Organic Matter (DOM) in Lakes on the Canadian Precambrian Shield and Links to Watershed Characteristics

Abstract: In the present study, we explored the use of various optical parameters to detect differences in the composition of the dissolved organic matter (DOM) in a set of lakes that are all located on the Canadian Precambrian Shield, but within which Cu and Ni speciation predictions were previously shown to diverge from measured values in some lakes but not in others. Water samples were collected with in situ diffusion samplers in 2007 (N = 18 lakes) and 2008 (N = 8 lakes). Significant differences in DOM quality were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
26
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 43 publications
5
26
0
Order By: Relevance
“…Although a detailed description of the study sites can be found in Mueller et al [20] a brief description is given here. Lake water was collected from lakes in two different regions on the Canadian Shield: near Rouyn-Noranda in north-western Quebec and near Sudbury in north-central Ontario.…”
Section: Study Areamentioning
confidence: 99%
See 4 more Smart Citations
“…Although a detailed description of the study sites can be found in Mueller et al [20] a brief description is given here. Lake water was collected from lakes in two different regions on the Canadian Shield: near Rouyn-Noranda in north-western Quebec and near Sudbury in north-central Ontario.…”
Section: Study Areamentioning
confidence: 99%
“…pH and concentrations of DOC and major cations) is known to be minimal within many of the sampled lakes. [3] Lake water was collected passively using equilibrium diffusion sampling as described in Fortin et al [3] and Mueller et al [20] Briefly, 250-mL polypropylene jars (Nalgene, Nalge Nunc International Corporation, Rochester, NY) topped with custom-made plastic lids fitted with a 0.2-mm filter membrane (HT Tuffryn Membrane, Pall Canada Ltd, Ville St-Laurent, QC, Canada) were filled with Milli-Q (Millipore, EMD Millipore, Billerica, MA) ultrapure water (.18 MO cm) and fixed to plastic rods that were anchored to the lake bottom. The samplers were installed at a depth of 1 m from the lake surface and left to equilibrate for 13 to 14 days.…”
Section: Study Areamentioning
confidence: 99%
See 3 more Smart Citations